From bad to worse: Poverty impacts of food availability responses to weather shocks - Koo, Jawoo; Mamun, Abdullah; Martin, Will (International Association of Agricultural Economists, 2021)
Since Amartya Sen's famous work on Poverty and Famines, economists have understood that the impacts of food market shocks on the poor depend much more on their impacts on households’ incomes and access to food than on overall food availability, and that availability-based policies frequently exacerbate adverse impacts on household welfare. Perhaps because household-level impacts are not directly observable many makers have continued to rely on availability-oriented policies such as export bans. In the Zambia case considered in this article, export bans imposed in response to an El Niño event appear to have greatly exacerbated the small increase in poverty resulting from the weather shock. The combination of household-level data and crop models used in this article allows us to assess the impacts of weather and price shocks at the household level, and to evaluate the suitability of availability-based policies for dealing with weather shocks. These analytical techniques can also help identify the households and regions adversely affected, and design policies to improve poor consumers’ access to food.